Complete sequence of the IncA/C 1 plasmid pCf587 carrying bla PER-2 from citrobacter freundii - Ruggiero, Melina (2018)
The bla PER-2 -harboring plasmid pCf587 (191,541 bp) belongs to lineage IncA/C 1 and is closely related to pRA1. It contains a large resistance island including the bla PER-2 gene between two copies of ISKox2-like elements, the toxin-antitoxin module pemK-pemI, several other resistance genes inserted within a Tn2 transposon, a Tn21-like structure, and a class 1 integron. pCf587 belongs to sequence type 13 (ST13), a new plasmid multilocus sequence typing (pMLST) ST.